The Linguistic Landscape of Ruteng City: A Study on Shop Signs Owned by Chinese and Indigenous Indonesian Ethnic Groups - Moon, Yuliana Jetia; Syahfitri, Dian; Hasbul, Wahyuni; Wirahyuni, Kadek (Bahasa Indonesia Prima, 2025)
The main question in this research is how the shop signs owned by Chinese and Indigenous Indonesian communities in Ruteng represent ethnic identity and cultural values, reflect multicultural dynamics, and illustrate the process of acculturation within the public space. The objective of this research is to describe the forms of language representation used in the shop signs owned by Chinese and Indigenous Indonesian communities in Ruteng; to identify the cultural values reflected in the language choices and visual appearances of the shop signs; and to analyze how multicultural dynamics and cultural acculturation processes are manifested in the linguistic landscape of Ruteng City. This research used a qualitative approach, utilizing methods of observation, photography, interviews, content analysis, and literature study. The data were analyzed using content and thematic analysis techniques. The research results show that Indigenous Indonesian store owners tend to choose names and colors based on personal preferences and the concept of modernity. In contrast, Chinese store owners preserve cultural values by selecting names that carry meanings of luck, harmony, and feng shui principles. Chinese ethnic stores tend to have symbolic functions, whereas Indigenous Indonesian stores tend to be informative. The language used in Chinese ethnic stores is monolingual, while Indigenous Indonesian stores use both monolingual and bilingual languages. The multicultural dynamics, viewed through the lens of the linguistic landscape in Ruteng, show an acculturation process characterized by harmonious social integration, where cultural identity is preserved without constraining social interaction. Ruteng City emerges as an example of inclusive and dynamic multiculturalism.